Environmental Care Character as a Managed Chain: A Strategic Management Analysis of the Adiwiyata Program in an Islamic Primary School - Mukhlisoh Mukhlisoh; Ade Aspandi; Suhatma Suhatma (Universitas Nurul Jadid, 2026)
Environmental degradation driven by plastic waste has intensified the demand for schools to cultivate environmental care as a dimension of student character. Many environmental programs, however, emphasize activity over the management required to make their outcomes endure. This study examines the Adiwiyata program through the lens of strategic management, aiming to analyze students' environmental care character, to examine how the program is implemented, and to evaluate how its strategic management contributes to strengthening that character. A qualitative descriptive design was employed, with the researcher serving as the primary instrument. Data were gathered through observation, in-depth interviews, and documentation, and were subsequently analyzed using the interactive analysis model and validated through triangulation across sources, techniques, and time. The findings demonstrate that environmental care develops as a layered and gradual achievement, sustained jointly by habituation, peer influence, and the discipline of school regulation, and maturing unevenly across grade levels. The program proved strong in formulation and implementation, although it remained constrained by workload, space, and funding. The principal implication is that policy, curriculum, participatory activity, and infrastructure function as an interdependent chain, which provides educational managers with a diagnostic instrument for identifying where character formation breaks down rather than a checklist of activities to complete.